Two working document: Technical consultation on the integration of statistical and agricultural market information services - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
Technical consultation on the integration of statistical and agricultural market information services.